Effects of electrical lesion of basolateral amygdala nucleus on rat anxiety‐like behaviour under acute, sub‐chronic, and chronic stresses - Ranjbar, Hoda; Radahmadi, Maryam; Reisi, Parham; Alaei, Hojjatallah (Clinical and experimental pharmacology & physiology, 2017)
Summary Stress contributes, as a risk factor, to such psychological disorders as anxiety. The effects of electrical lesions in the basolateral amygdala nucleus (BLA) were investigated on the locomotor activity and anxiety‐like behaviour in different stress durations. For this purpose, rats were randomly allocated to control, sham, and experimental groups, the latter including groups with and without BLA nucleus subjected to acute, sub‐chronic, and chronic stress conditions for 1, 7, and 21 days, respectively, applied 6 h/d. The induced anxiety behaviour was evaluated using the open field test (OFT) while other variables were measured. Findings revealed that sub‐chronic stress led to significantly reduced (P<.05) anxiety behaviours as measured by entries into and the time spent in the centre area while it also led to significant impairments in exploratory and locomotor activities, indicating intensified anxiety‐like behaviour. BLA lesion affected rat behaviour differently such that it significantly (P<.05) decreased fear under sub‐chronic and chronic stress conditions as evidenced by the subjects’ greater tendency to enter the centre area in the open field test and their increased number of rearing events (P<.01). However, BLA lesion led to no significant decrease in the locomotor activity of subjects exposed to sub‐chronic or chronic stress conditions as compared with those in similar groups but without BLA lesion. Finally, BLA lesion was found not only to decrease significantly (P<.01) adrenal gland and body weights, particularly under sub‐chronic stress, but also to play a critical role in modulating adrenal functions by decreasing adrenal gland weight, and thereby reducing depression‐like symptoms.